SCHEMES OF SPATIAL PLANNING OF COMMUNITIES – THE BASIS OF DEVELOPMENT OF RURAL TERRITORIES (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article analyses the main problems of development of rural territories in the conditions of decentralization concerning modern realities. Rural territories traditionally took special place in the formation of demographic, economic, resource-production and social-humanitarian potential of Ukraine. The present stage of social development of rural territories concerning change of the method of agricultural production and introduction of industrial technologies of growing  agricultural  crops and cattle care is characterized by the gradual extinction of “non-perspective” rural settlements The complex plan of spatial development of united territorial communities must become the road map of rural territories development. The solving of rural territories development problems must include the following measures: the formation of regulatory framework in the sphere of rural population employment, the creating of powerful consulting service, professional-education training of personnel, which will increase  the quality of workforce, that will allow to save and create the new working places, will promote the development of entrepreneurship and independent employment of population.
Keywords: rural territories, administrative-territorial reform, agricultural grounds, land protection, farms, population employment.